A Review On Oil-Based Nanofluid As Next-Generation Insulation For Transformer Application - Md Din, Muhamad Faiz; Hassan, Muhammad Zahir; Suhaimi, Sabrina N.; A. Rahman, Abdul R.; Ishak, Mohd Taufiq; Jusoh, Mohd Taufik (Hindawi Limited, 2020)
Due to the increasing demand on developing good insulation, several researchers have performed experimental studies to prove the effectiveness and capabilities of transformer oil. This is done by suspending nanosized solid particles in the oil (nanofluid) for transformer applications. In brief, this paper presents a compilation of research studies which is divided into three parts. Part I discuss the preparation of the nanofluid which involves different types of nanomaterials, the optimal amount of concentrations, and applicable synthesisation methods for producing stably suspended nanofluids. In Part II, the nanofluid’s performances including the electrical breakdown voltages, impulse tests, and thermal and dielectric behaviour are reviewed in depth and compared. Part III emphasizes the limitation of nanofluids. Most researchers have agreed that appropriate concentrations of nanomaterials and the preparation method for nanofluids mainly affect the performance of nanofluids especially in terms of electrical properties. Meanwhile, types of nanomaterials and base oil also play a vital role in producing nanofluids as a better alternative transformer oil. However, among a few researchers, there are concerns regarding the issue of agglomeration and inconsistencies of findings that need to be resolved. Therefore, a few aspects must be taken into consideration to produce the next generation of high heat dissipation insulation.